2020
DOI: 10.5194/hess-24-5077-2020
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in nonstationary frequency analysis of South Korea's daily rainfall peak over threshold excesses associated with covariates

Abstract: Abstract. Several methods have been proposed to analyze the frequency of nonstationary anomalies. The applicability of the nonstationary frequency analysis has been mainly evaluated based on the agreement between the time series data and the applied probability distribution. However, since the uncertainty in the parameter estimate of the probability distribution is the main source of uncertainty in frequency analysis, the uncertainty in the correspondence between samples and probability distribution is inevita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…As sampling algorithms, Metropolis-Hastings, Gibbs Sampling, Hamiltonian Monte Carlo, and No-U-Turn Sampler are widely used. In this study, the Metropolis-Hastings algorithm [35][36][37][38] was used, which is relatively simple and easy to apply and has a low computational cost compared to other algorithms in some cases. First, the values of the parameters estimated from the rainfall fields of two different storm events are presented in Table 4.…”
Section: Results From the Elevation-associated Rainfall Field Estimat...mentioning
confidence: 99%
“…As sampling algorithms, Metropolis-Hastings, Gibbs Sampling, Hamiltonian Monte Carlo, and No-U-Turn Sampler are widely used. In this study, the Metropolis-Hastings algorithm [35][36][37][38] was used, which is relatively simple and easy to apply and has a low computational cost compared to other algorithms in some cases. First, the values of the parameters estimated from the rainfall fields of two different storm events are presented in Table 4.…”
Section: Results From the Elevation-associated Rainfall Field Estimat...mentioning
confidence: 99%
“…Furthermore, studies based on frequency analyses have revealed that climate change can alter the distribution parameters of extreme events, that is, distribution of extremes can have non-stationary characteristics over time, which can change the occurrence of probability [23][24][25][26][27]. However, under changing climatic conditions, frequency, and probability analyses of hydroclimatological variables should be conducted considering possible nonstationarities [28][29][30]. Precipitation events are random processes and making good predictions are crucial, especially for extreme events within this random framework.…”
Section: Introductionmentioning
confidence: 99%